Knowledge Absorptive: The New Paradigm in Educational Administration - Siririn, Jakkrit (National Interest, 2021)
The Educational Administration theory have a diversity of changes and as quick as society moves towards a globalization, 21st century, digital era, ASEAN and the Education 4.0 concepts. Whether it happens to the new paradigm such as Non-Cognitive Skills, STEM, World Class Standard School, Civil-state School or Corporate University meanwhile it comes to educational administration in basic education for coincides with the existing Corporate University. The two institutions format also requires a new paradigm called Knowledge Absorptive as a new tool of educational administration in modern times. On the basis of knowledge management and its influence on the management of modern enterprises, rather than by the general theory of knowledge management applications with educational administration. Educational organizations will be more developed than at present, so knowledge management is at the heart of one of the educational administration. In addition, knowledge management and another idea that is interested in educational administration in present day. Especially when the idea of establishing a new institution, the private sector organizations have established their own institutions, including the public school called Civil-state School and the Corporate University, the process leading to Knowledge Absorptive. The enterprise development just improve the ability of the processes within the organization. The changed is more important, it is innovation and a new paradigm in the educational administration today.